2016
DOI: 10.1016/j.gie.2015.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative diagnostic performance of volumetric laser endomicroscopy and confocal laser endomicroscopy in the detection of dysplasia associated with Barrett’s esophagus

Abstract: Background and Aims Probe-based confocal laser endomicroscopy (pCLE) and volumetric laser endomicroscopy (VLE) (also known as frequency domain optical coherence tomography) are advanced endoscopic imaging modalities that may be useful in the diagnosis of dysplasia associated with Barrett’s esophagus (BE). We performed pCLE examination in ex-vivo EMR specimens and compared the diagnostic performance of using the current VLE scoring index (previously established as OCT-SI) and a novel VLE diagnostic algorithm (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
125
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 21 publications
2
125
1
Order By: Relevance
“…The NvisionVLETM system was used in all studies [23][24][25][26][27][28][29]. Volumetric laser endomicroscopy is a second-generation optical coherence tomography.…”
Section: Equipment and Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…The NvisionVLETM system was used in all studies [23][24][25][26][27][28][29]. Volumetric laser endomicroscopy is a second-generation optical coherence tomography.…”
Section: Equipment and Techniquesmentioning
confidence: 99%
“…Long segment imaging can be obtained with an axial resolution of 7 µm, a transverse resolution of about 30 µm, and can reach an imaging depth of up to 2 to 3 mm. A total of 1200 images can be obtained in 96 secs [23][24][25][26].…”
Section: Equipment and Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, clinical VLE prediction models were developed for BE neoplasia showing good accuracy. 6,7 However, pilot studies using ex vivo and in vivo VLE data may suggest that full scan VLE interpretation by experts remains difficult. 8,9 In vivo case reports suggested that VLE could detect additional neoplasia, however, clinical trials in larger sample size are necessary to confirm these findings.…”
Section: Introductionmentioning
confidence: 99%